2014
DOI: 10.4103/0972-5229.144015
|View full text |Cite
|
Sign up to set email alerts
|

Optic nerve sheath diameter as a marker for evaluation and prognostication of intracranial pressure in Indian patients: An observational study

Abstract: Background and Aims:The aim was to evaluate efficacy of optic nerve sheath diameter (ONSD) by ultrasound as a noninvasive method for detecting raised intracranial pressure (ICP) in intensive care unit, to compare with computed tomography/magnetic resonance imaging (MRI) findings of raised ICP and to prognosticate ONSD value with treatment.Materials and Methods:We conducted a prospective, observational study on 101 adults by including 41 healthy individuals in group A as control and 60 patients in group B admit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
33
2
12

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 61 publications
(51 citation statements)
references
References 31 publications
2
33
2
12
Order By: Relevance
“…They have not commented on the presence or absence of MRI findings of raised ICP and hence have not corroborated the cut-off values of ONSD for raised ICP in Indian patients which as per Shirodkar et al . [ 14 ] was found to be somewhat less than those from previous studies.…”
contrasting
confidence: 58%
See 1 more Smart Citation
“…They have not commented on the presence or absence of MRI findings of raised ICP and hence have not corroborated the cut-off values of ONSD for raised ICP in Indian patients which as per Shirodkar et al . [ 14 ] was found to be somewhat less than those from previous studies.…”
contrasting
confidence: 58%
“…The current authors have selected cut-off values of 4.6 mm for females, and 4.8 mm for males in accordance to a study by Shirodkar et al . [ 14 ] on 101 Indian patients who demonstrated a high level of sensitivity and specificity with these cut-off values for the diagnosis of intracranial hypertension as evident on CT or MRI imaging. However, the current authors have limited themselves to comparing the numerical accuracy of ONSD values obtained with USG and MRI.…”
mentioning
confidence: 99%
“…[ 2 18 ] In our previous study, we performed the efficacy of ONSD measurement by USG to predict intracranial hypertension. [ 19 ] Using cut-off values of 4.6 mm for females, and 4.8 mm for males, they found a high level of sensitivity and specificity for the diagnosis of intracranial hypertension evident on computed tomography (CT) or MRI.…”
Section: Discussionmentioning
confidence: 99%
“…2). Shirodkar et al found ONSD cutoffs (4.6 mm for females; 4.8 mm for males) that had a sensitivity between 84.6 % (females) and 75 % (males) and a specificity of 100 % (both genders) for the detection of MRI signs of elevated ICP, such as midline shift, edema, and effacement [33]. Similarly, a study of 24 adult patients compared ONSD by ocular ultrasound to CT findings of midline shift, sulcal effacement with significant edema, third ventricle collapse, and hydrocephalus, and using a cutoff of 5.0 mm, they achieved a sensitivity of 100 %, specificity of 75 %, PPVof 95.4 %, and NPVof 100 % [34].…”
Section: Ocular Ultrasoundmentioning
confidence: 97%